Level of attitude, behavior, and awareness of senior high school students toward environmental conservation - Jeffry M. Saro; Jecel D. Taray; Jemuel S. Cinso; Bonifacio S. Ingaling; Merry Joy A. Enguio; Cynne Paul B. Hayon (University of Muhammadiyah Malang, 2025)
Environmental issues such as global warming, ozone layer depletion, and biodiversity loss emphasize the urgent need for ecological conservation and awareness. Despite the accessibility of environmental education and media resources, gaps persist in translating this knowledge into sustainable attitudes and behaviors. This study investigated senior high school STEM students' environmental attitudes, behaviors, and awareness within the Agusan del Sur Division. It examined how understanding and attitudes influenced ecological behaviors and identified specific attitudes that most affected awareness. Employing a sequential explanatory research design, the study combined quantitative data from surveys with qualitative insights from interviews to provide a holistic understanding of participants' ecological perspectives. A validated questionnaire, adapted from the Environmental Attitude Inventory, measured dimensions such as anthropocentric and eco-centric attitudes, sustainability practices, and environmental responsibility. Results revealed that participants generally demonstrated positive environmental attitudes (μ = 3.57), neutral ecological behaviors (μ = 3.40), and positive environmental awareness (μ = 3.60). Pearson correlation analyses showed significant positive relationships between attitudes, behaviors, and awareness, with ecological behavior and awareness exhibiting the strongest association (r = 0.78).The thematic analysis of interview responses highlighted ten emerging themes: waste reduction practices, energy conservation at home, participation in recycling programs, support for environmental campaigns, educating peers on environmental issues, sustainable consumption, climate change awareness, use of public transportation, involvement in conservation projects, and advocacy for renewable energy. These findings emphasize the need to cultivate positive environmental attitudes to enhance ecological responsibility and awareness among students. The study recommends integrating long-term educational strategies and socio-cultural analyses to sustain these efforts and promote impactful conservation initiatives, addressing the global imperative for environmental stewardship.